Investigating the technology acceptance among student teachers in Malaysia : an application of the Technology Acceptance Model (TAM). - Wong, Su Luan; Teo, Timothy (De La Salle University, Manila, 2009)
This study investigated 245 Malaysian student teachers' self-reported intentions to use (ITU) computers. Using the Technology Acceptance Model (TAM) as a research framework, this study found perceived usefulness (PU) of computer technology, perceived ease of use (PEU), and attitude towards computer use (ATCU) to be significant determinants of ITU. Results obtained using structural equation modelling revealed that (I) PEU significantly influenced PU, (2) both PU and PEU significantly influenced ATCU, and (3) both PU and ATCU significantly influenced ITU. In essence, the results of this study present some evidence that TAM serves as a valid model to predict technology acceptance among student teachers in Malaysia.